-1/5x+12=2/5x+6

Simple and best practice solution for -1/5x+12=2/5x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/5x+12=2/5x+6 equation:



-1/5x+12=2/5x+6
We move all terms to the left:
-1/5x+12-(2/5x+6)=0
Domain of the equation: 5x!=0
x!=0/5
x!=0
x∈R
Domain of the equation: 5x+6)!=0
x∈R
We get rid of parentheses
-1/5x-2/5x-6+12=0
We multiply all the terms by the denominator
-6*5x+12*5x-1-2=0
We add all the numbers together, and all the variables
-6*5x+12*5x-3=0
Wy multiply elements
-30x+60x-3=0
We add all the numbers together, and all the variables
30x-3=0
We move all terms containing x to the left, all other terms to the right
30x=3
x=3/30
x=1/10

See similar equations:

| (X+2)^2=x^2+4x+4 | | G(x)=x2+5x+-3 | | 6x+10+(-3x)=4x*10 | | |m-3|=8 | | 3c-15=-c | | 7−5+3x−1=4x+2 | | -8x-36=-5(1+8x)+x | | a+5=-18 | | n+153=-4+8 | | -3(3z-8)=2z-31 | | 4a-3=-55 | | (X+2)^2=x^2+4+4 | | 5r+9=-6 | | 8.50x=1,000+2.50x | | 5+10x=25 | | 5(x+8)=-37-6x | | 1/5x+12=2/5x+6 | | 5n-4=-2 | | b/6 = -2 | | 4r+2=42 | | -3(2x+18)=6 | | 3-3x=3(1-x) | | -5c=-40 | | -49(-3x-6)=108 | | 1/6y+2=-7 | | 9k=6=8k+13 | | 18y-14y=12. | | 8m-9m=5m+10m | | 5x+27=-×-3 | | 1+8m=6m+5 | | 3m-5=5+5m-7m | | 2x-0,33=1 |

Equations solver categories